2011
DOI: 10.1016/j.jbiomech.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Shear strength and toughness of trabecular bone are more sensitive to density than damage

Abstract: Microdamage occurs in trabecular bone under normal loading, which impairs the mechanical properties. Architectural degradation associated with osteoporosis increases damage susceptibility, resulting in a cumulative negative effect on the mechanical properties. Treatments for osteoporosis could be targeted toward increased bone mineral density, improved architecture, or repair and prevention of microdamage. Delineating the relative roles of damage and architectural degradation on trabecular bone strength will p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 61 publications
(97 reference statements)
1
16
0
Order By: Relevance
“…Bone is considered to be stronger in compression and weakest in tension or shear. Most of the earlier studies have been focused on the determination of shear properties of trabecular bone [4][5][6] whereas in very limited studies shear behavior of cortical bone have been discussed based on torsional and three point bending methods [7][8]. Turner et al [9] observed that torsion often causes spiral fracture plane that corresponds to tensile rather than shear failure.…”
mentioning
confidence: 99%
“…Bone is considered to be stronger in compression and weakest in tension or shear. Most of the earlier studies have been focused on the determination of shear properties of trabecular bone [4][5][6] whereas in very limited studies shear behavior of cortical bone have been discussed based on torsional and three point bending methods [7][8]. Turner et al [9] observed that torsion often causes spiral fracture plane that corresponds to tensile rather than shear failure.…”
mentioning
confidence: 99%
“…While the ultimate shear strength of sheep cancellous bone has yet to be reported, the ultimate shear strength of bovine femoral cancellous bone has been measured at 6.57±2.46 MPa. 33 Looking to Figure 5A, it can be seen that the majority of the tested sample's ultimate shear strengths were within the range of cancellous bone. Unlike the TPS implants, the bone-implant interface of all the AM groups remained intact after ≥ 2500N of force; this indicates that the bone-implant interface is stronger that than the surrounding cancellous bone.…”
Section: Discussionmentioning
confidence: 89%
“…In the previously mentioned study by Garrison et al , 5 damage was first induced in bovine trabecular bone specimens by either low or high amounts of compressive overloading (2.5 or 4.5 % strain, respectively). Specimens were then tested to failure by shear loading to simulate the unusual loading pattern that may occur in a fall.…”
mentioning
confidence: 99%
“…Importantly, multiple regression analyses indicated that bone toughness was more sensitive to BV / TV than to damage quantity. Thus, Garrison et al 5 Commentary net beneficial effect on bone. The results concur with their prior work showing that bone density and microarchitecture have a greater influence than microdamage on the toughness of bovine trabecular bone specimens tested in compression.…”
mentioning
confidence: 99%
See 1 more Smart Citation